Analysis of Poverty Determinants in The Bali Province 2015-2020 - Resky Tri Nur Said; Gatot Sasongko (MediaTrend, 2022)
Poverty is a long-term problem in economic development in a country, especially developing countries. This study aims to analyze the effect of economic growth, population, the number of unemployed (TPT), minimum wage, and human development index (IPM) on poverty in Bali Province. The approach used in this research is quantitative with secondary data obtained from the Indonesian Central Bureau of Statistics (BPS) for 2015-2020. The method used to analyze the factors that influence poverty in Bali Province is panel data regression. Based on the results of the study showed that partial economic growth has no effect on poverty. This condition occurs because economic growth in Bali Province has not been inclusive. The minimum wage and the Human Development Index have a negative effect on poverty so an increase in the minimum wage and the HDI will reduce poverty significantly. The number of unemployed and the total population have a positive effect on poverty in the Province of Bali. Simultaneously economic growth, population, number of unemployed (TPT), minimum wage, and human development index (IPM) have a significant effect on poverty in Bali Province.